Charting the Waters: Navigating Finnish American Folk Musics and Identity in the Pacific Northwest - Boughton, Devina (Taideyliopiston Sibelius-Akatemia, 2025)
Tutkin identiteetin rakentumista ja moninaisuutta pohjoismaalaisten siirtolaisten diasporayhteisöissä, ja ihmisiä joilla on niihin yhteyttä. Tutkin tätä tarkastelemalla kansanmusiikin ja muun kulttuuriperintöön liittyvän luovan toiminnan merkitystä amerikansuomalaisessa kulttuurissa ja identiteetin rakentumisessa Pacific Northwestin (PNW)2 alueella Yhdysvalloissa. Päätutkimuskysymykseni on: Millainen rooli kansanmusisoimisella (tai kansanmusiikilla ja musisoimisella) on pohjoisamerikansuomalaisissa että pohjoismaisen siirtolaisdiasporan identiteetin rakentamisessa Pacific Northwestin (PNW) alueella Yhdysvalloissa. Ymmärtääkseni amerikansuomalaisen identiteetin ajankohtaisuutta Pohjois-Amerikassa vuonna 2025, hyödynnän omaa positiotani Suomessa asuvana amerikansuomalaisena. Käytän autoetnografiaa vastatessani tutkimuskysymykseen omaa kokemustani reflektoiden. Tutkimuksessani hyödynnän myös etnografiaa, ja haastattelen neljää PNW:ssä asuvaa henkilöä, joilla on musiikillinen yhteys ja miten tämä aiheuttaa niiden yhteyttä identiteetteihin sekä kulttuureihin ymmärtämiseen. Käsitän tutkimukseni verkkona, verkostona, tai puuna, joka kasvaa sekä juurista että oksista. Tutkimusten tulosten mukaan tila suomalaiseen kulttuuriperintöön syventymiselle – joko perheen tai muun yhteisön avulla – yhdistettynä taiteelliseen/musiikilliseen toimintaan voi luoda merkityksen tunteita, yhteisöllisyyttä ja vahvistaa kokemusta identiteetistä. Väitän, että tällaisen tilan tekeminen luovuudelle on toiminnalle on yhtä tärkeää kuin luotava musiikki. Tämä tukee uhanalaisten perinteiden muovautumista ja jatkuvuutta nykyajassa, edistää ymmärrystä aikakausien välisistä yhteyksistä ja kuviteltujen todellisuuksien hyödyntämistä luomistyössä. Lisäksi tutkimus lisää tietoisuutta muuttuvista ja moninaisista näkökulmista pohjoisamerikansuomalaiseen ja pohjoismaiseen diasporakulttuuriin.

I will explore the multiplicity and definitions of identity formation in generational Nordic Diaspora immigrant communities, and people connected to those communities. This will be explored through the lens of folk musics, and additional practices of creativity within cultural heritage in conjunction with Finnish American culture and identity formation in the Pacific Northwest (PNW)1 region of the United States. My main research question explores: How does folk music making play a role in Finnish North American and Nordic diaspora identity formation in the Pacific Northwest of the United States? In order to understand the relevance of Finnish North American identity in the Pacific Northwest in 2025, I use my own positionality as a Finnish North American musician living in Finland as an example. I also use autoethnography to answer my research question from a perspective of self-reflection. Pairing this with ethnography, I interview four people living in the PNW who engage with Finnish and Nordic American culture with musical practices connected to Finland and/or Norway and how this impacts their connection with understanding their identities and relationship to cultural heritage. I imagine this research like a network, a web, a tree branching out from its roots and trunk. My results show that making space to dive into Finnish cultural heritage(s), whether through family or through adjacent community, and connecting with them through artistic practices such as music can help provide meaning, create community and senses/facets of identity. I argue that the space for this creativity music making is just as important as the music or artistic practice itself being created. This allows endangered traditions to change and continue with modern times, understand the connection of different times and elements, and interface with imagined realities as a powerful tool for creation. The results of my thesis can be used for example to examine meaningful ways to develop and understand how identity(s), community building, and creative music making as well as place and space are useful in a diasporic cultural heritage context. Additionally, this thesis gives awareness to ever-shifting and complex dynamics and perspectives of Finnish and Nordic diaspora culture in the United States.
Keywords: Finnish North Americans; United States; Finnish folk music; Nordic folk music; musicking; identity formation; Pacific Northwest; community music; Finnish Americans; diaspora; culture; folk music (traditional music); tradition; Finnish language; cultural heritage; Global Music